Performance - a Determining Factor in the Public Health System from Romania and the EU - Panaitescu, Manuela; Andronic, Bogdan (Journal of Danubian Studies and Research, 2023)
Performance in the health system is one of the determining factors of the growth and development of a state, because the well-being of people depends on the quality of the health system, and on the life expectancy of citizens. A healthy person directly contributes to the increase of labor productivity, as well as its contribution to the state budget, through the payment of taxes. Performance in the health system can only be achieved if we understand that at the center of the system is the patient, with his needs for medical services that must be met safely.